Interfacial self-assembly of SiO2–PNIPAM core–shell particles with varied crosslinking density. Issue 30 (18th July 2022) - Ickler, Maret; Menath, Johannes; Holstein, Laura; Rey, Marcel; Buzza, D. Martin A.; Vogel, Nicolas
Abstract : The effect of crosslinker content and core size on the interfacial self-assembly of batch-type PNIPAM@SiO2 core–shell particles was studied, revealing parameter windows for chain phases, rhomboid packing and stable d = 448 nm non-close packed cores. Abstract : Spherical particles confined to liquid interfaces generally self-assemble into hexagonal patterns. It was theoretically predicted by Jagla two decades ago that such particles interacting via a soft repulsive potential are able to form complex, anisotropic assembly phases. Depending on the shape and range of the potential, the predicted minimum energy configurations include chains, rhomboid and square phases. We recently demonstrated that deformable core–shell particles consisting of a hard silica core and a soft poly( N -isopropylacrylamide) shell adsorbed at an air/water interface can form chain phases if the crosslinker is primarily incorporated around the silica core. Here, we systematically investigate the interfacial self-assembly behavior of such SiO2 –PNIPAM core–shell particles as a function of crosslinker content and core size. We observe chain networks predominantly at low crosslinking densities and smaller core sizes, whereas higher crosslinking densities lead to the formation of rhomboid packing. We correlate these results with the interfacial morphologies of the different particle systems, where the ability to expand at the interface and form a thin corona at the periphery depends on the degree of crosslinking close to the core. We perform minimum energy calculations based on Jagla-type pair potentials with different shapes of the soft repulsive shoulder. We compare the theoretical phase diagram with experimental findings to infer to which extent the interfacial interactions of the experimental system may be captured by Jagla pair–wise interaction potentials.